Pengelolaan Dana Tabarru dan Proses Klaim Asuransi Kesehatan Syariah pada Bank Muamalat Cabang Sumber - Hafizd, Jefik Zulfikar; Al-Hanif, Elbayati; Khoirudin, Ahmad; Fatakh, Abdul (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2025)
This study aims to analyze the management of tabarru funds in sharia health insurance and the sharia health insurance claims process at Bank Muamalat Syariah. The method used in this study is a literature study method, and through a qualitative descriptive approach. Sharia Health Insurance has a solid legal basis, firmly rooted in the principles of Islamic sharia (ta'awun, avoiding gharar and usury) and supported by positive Indonesian law (Law No. 40 of 2014) and DSN-MUI Fatwas (No. 21, 52, 53) which regulate general guidelines, Wakalah bil Ujrah contracts, and Tabarru' contracts. All operations are based on the main principles of Takaful (mutual responsibility), Wakalah (representation), and Tabarru' (voluntary contribution) for the benefit of the community broadly and sustainably. In practice, Bank Muamalat's Sumber Branch, in collaboration with trusted insurance partners, strictly manages the Tabarru' Fund, which is separated from the company's funds and invested in halal instruments such as Sukuk and Sharia Deposits. To ensure fairness, the Claims Process is designed to be efficient through a Cashless or Rembes mechanism, while still implementing strict health history verification (anti-fraud) to exclude pre-existing conditions, ensure transparency, and ensure compliance with the agreed-upon agreements to maintain participant trust.